2020
DOI: 10.4018/978-1-5225-9829-9.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Management Information Systems for Higher Education Institutions

Abstract: Modern universities thrive on the information gathered through well-managed information systems. The overall process of developing and maintaining Academic Information System (AIS) all within the university and without any external assistance is generally regarded as a mark of achievement. This chapter deals with various aspects of AIS such as requirements, development, testing, overall security, etc. Two major options, developing AIS from scratch and deploying a commercially available software solution, are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The business processes depend upon individual firm strategies and hence digital platforms will need to be designed to meet their own objectives as opposed to the general or fixed business model (Musti, 2020; Vertabelo, 2019). Most P2P firms are offering different products such as money transfer, wallets and semi-online payment banks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The business processes depend upon individual firm strategies and hence digital platforms will need to be designed to meet their own objectives as opposed to the general or fixed business model (Musti, 2020; Vertabelo, 2019). Most P2P firms are offering different products such as money transfer, wallets and semi-online payment banks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…University management information systems consider the peculiarities of such institutions as educational institutions. The authors of the academic information system research justify the expediency of complex automation and internal development of software modules of such a system [10].…”
Section: Introductionmentioning
confidence: 99%
“…Educational institutions globally have implemented various strategies to manage and administer their teaching and learning data [1] [2]. The study by [3] highlighted the importance and impact of management information systems on studies conducted at the universities in Turkey and Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of management information system, organisations do not recognize all the aspect required to make a success out of its implementation. It is identified that the most important aspect that has been ignored or not provided enough attention is the technology and people [2]. The lack of people"s involvement is noted to have a negative impact on the system"s performance.…”
Section: Introductionmentioning
confidence: 99%